2017
DOI: 10.1007/s00213-017-4611-z
|View full text |Cite
|
Sign up to set email alerts
|

A schizophrenia relevant 5-Choice Serial Reaction Time Task for mice assessing broad monitoring, distractibility and impulsivity

Abstract: The 5-Choice Serial Reaction Time Task (5-CSRTT) is an automated test for rodents allowing the assessment of multiple cognitive measures. Originally designed to assess cognitive deficits relevant to attention deficit hyperactivity disorder, it has been widely used in the investigation of neural systems of attention. In the current study, we have set up a modified version, which reduced the training phase to only 8-9 days with minimal food deprivation and without single-housing. Furthermore, based on evidence t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 96 publications
3
10
0
Order By: Relevance
“…green flashing lights) randomly presented within the same session to more directly compare attentional performance with that of non-distractor trials, in order to avoid potential habituation processes found with noises 37 and confusion with the use of house lights 59 as reported in adults. Finally, as also previously discussed 47 , we were able to demonstrate clear differences between the SARAT and distractor paradigms. Briefly, the combination of tasks used in the current work show that the cue lights were not simply treated as target stimulus lights, as only non-predictive cues decreased the accuracy and that this was directly proportional to the degree of unpredictability (e.g.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…green flashing lights) randomly presented within the same session to more directly compare attentional performance with that of non-distractor trials, in order to avoid potential habituation processes found with noises 37 and confusion with the use of house lights 59 as reported in adults. Finally, as also previously discussed 47 , we were able to demonstrate clear differences between the SARAT and distractor paradigms. Briefly, the combination of tasks used in the current work show that the cue lights were not simply treated as target stimulus lights, as only non-predictive cues decreased the accuracy and that this was directly proportional to the degree of unpredictability (e.g.…”
Section: Discussionsupporting
confidence: 85%
“…To test whether the SARAT and the Distractor paradigms could grasp distinct aspects of attentional control in adolescent mice, we further implemented these two paradigms (Fig. 2 : SARAT v2 and Distractor v2 paradigms), as done in adult mice 47 . In particular, with the SARAT version 2, we directly linked mice performance to the number of presented pre-cues (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For rodents, discrete elements of attentional processes such as sustained and focused attention, impulse control, perseverative and reactivity-related functions can be effectively studied. In particular, one of the most effective and extensively used task in rodents is the 5-Choice Serial Reaction Time Task (5-CSRTT) which allows for measures of general attention, impulse control and processing speed (Carli et al, 1983;Ciampoli et al, 2017;Huang et al, 2017;Mereu et al, 2017;Robbins et al, 1993;Robbins, 2002;Voon et al, 2014). Conversely, the Distractor Condition Sustained Attention Task (dSAT) and the 5-Choice Continuous Performance Test (5C-CPT) are operant -based tasks developed as signal-detection tasks first in rodents (Barnes et al, 2012;Bushnell, 1999;Ciampoli et al, 2017;Huang et al, 2017;McGaughy and Sarter, 1995;Mereu et al, 2017;Mohler et al, 2001;Nuechterlein et al, 2009;Young et al, 2009) and then redesigned for humans, providing clinical translatability (Demeter et al, 2008;Young et al, 2013).…”
Section: Attentionmentioning
confidence: 99%
“…In particular, one of the most effective and extensively used task in rodents is the 5-Choice Serial Reaction Time Task (5-CSRTT) which allows for measures of general attention, impulse control and processing speed (Carli et al, 1983;Ciampoli et al, 2017;Huang et al, 2017;Mereu et al, 2017;Robbins et al, 1993;Robbins, 2002;Voon et al, 2014). Conversely, the Distractor Condition Sustained Attention Task (dSAT) and the 5-Choice Continuous Performance Test (5C-CPT) are operant -based tasks developed as signal-detection tasks first in rodents (Barnes et al, 2012;Bushnell, 1999;Ciampoli et al, 2017;Huang et al, 2017;McGaughy and Sarter, 1995;Mereu et al, 2017;Mohler et al, 2001;Nuechterlein et al, 2009;Young et al, 2009) and then redesigned for humans, providing clinical translatability (Demeter et al, 2008;Young et al, 2013). Similarly, based on the proven utility of the SARAT paradigm in distinguishing deficits in selective attention from broad monitoring alterations relevant to schizophrenia (Hahn et al, 2012;Hahn et al, 2006b), equivalent tasks have been developed in both adult and adolescent mice (Ciampoli et al, 2017;Huang et al, 2017;Mereu et al, 2017).…”
Section: Attentionmentioning
confidence: 99%